The Influence Of Work Ethic, Job Responsibilities And Office Infrastructure On Per-formance State Civil Apparatus Department Of Tourism And Culture In The Islands District Selayar - Dhian Trisnawaty; Muhammad Rusydi; Edi Jusriadi (Green Publisher Indonesia, 2024)
This research aims to determine and analyze the influence of work ethic, job responsibilities, office facilities and infrastructure on the performance of State Civil Apparatus at the Selayar Islands Regency Tourism and Culture Office. This type of research is quantitative research with a data collection instrument using a questionnaire method, with a sample size of 44 ASN people. Data analysis techniques use research instrument tests, classical assumption tests, multiple linear regression tests and partial tests (t tests) using the SPSS V.24 application. The research results show that: (1). Work ethic, job responsibilities, and office facilities and infrastructure have a positive and significant influence on the performance of State Civil Apparatus at the Selayar Islands Regency Tourism and Culture Office.